Macroeconomics - Dornbusch, Rudiger; Fischer, Stanley; Dornbusch, Rudiger (New York : McGraw-Hill, 1990)
A text dealing with the basic theory of macroeconomics. Revision and reorganization includes new material on international issues and controversies in macroeconomic theory and the open economy.
Includes bibliographical references and index.
Keywords: Macroeconomics